PERBEDAAN KELUHAN MUSKULOSKELETAL SEBELUM DAN SESUDAH PEMBERIAN WORKPLACE STRETCHING-EXERCISE PADA PERAWAT DI RSIA BADRUL AINI MEDAN TAHUN 2015 - anestia rovitri; halinda sari lubis; makmur sinaga (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT Nurse, as medical staff, has the highest risk to musculosekeletal disorders. The alternative solution is Workplace Stretching-Exercise (WSE) with stretching design. The aim of this research is to determine differences in musculoskeletal disorders before and after Workplace Stretching-Exercise (WSE) on nurses in Badrul Aini Child and Maternity Hospital. The type of this research is pre experimental with one group pretest posttest design. Samples based on total sampling as many as 34 people. Analysis of data using statistical test of Paired T-test with significant level of 95%. The results showed that musculoskeletal disorders mean is decrese in posttest compare with in pretest. Based on the Paired T-test is known there were differences in musculoskeletal disorders before and after Workplace Stretching-Exercise (WSE) (p.= 0,000). It is showed that Workplace Stretching-Exercise (WSE) can be one of alternative solution model to decrease musculoskeletal disorders. It is recommended that nurses perform Workplace Stretching-Exercise (WSE) in order to prevent and decrease musculoskeletal disorders